Life Cycles in the Methanogenic Archaebacterium Methanosarcina mazei - Robinson, Ralph W. (1986)
Methanosarcina mazei S6 and LYC were used to study the structure and differentiation of the aggregating methanogens. Cultures harvested under various conditions are described at the ultrastructural level. Cells of strain S6 are enclosed by a layer 12 nm thick in contact with the plasma membrane. In sarcinal colonies, cells are held in close association by a fibrous matrix up to 60 nm thick. Colony maturation was examined in strain S6 over a period of 1 year. Changes occurred in the shape and staining of individual cells. Also, various inclusion bodies were observed that either persist throughout colony maturation or are only found at certain growth stages. Two types of cores that are composed of double membranes in M. mazei S6 are described. One has a 90-nm diameter and contains electron-dense granules similar to those found in the cytoplasm. The other core type does not contain granules, is more numerous, and is found in older cultures. Two life cycles are described for M. mazei based on electron microscope examinations. A complex life cycle involving the release of single cells is described with two variations for strains S6 and LYC. When released cells of strain S6 are placed in fresh medium they can repeat the cycle. In addition, a limited cycle is described for both strains of M. mazei. This limited cycle contains the only sarcinal morphotypes observed in M. barkeri. When M. mazei S6 remains in the limited cycle and does not disaggregate in stationary phase, several types of possible resting forms are found.